ON THE SUCCESSFUL REARING OF MACROBRACHIUM ROSENBERGII IN MEDIUM PREPARED OF COMMON SALT AND SALT PAN RESIDUE - Prakash, Shree (Indian Journal of Fisheries, 2011)
The giant freshwater prawn Macrobrachlum rosenbergii is the most important among fishery resources due to its large size (250 - 300 mm) and highest market price (Rs. 100 - 150/kg). The farming of this prawn was initiated in Malaysia (Ling, 1969) and U.S.A. (Fujimura, 1972) and is now popularising rapidly in several Asian countries.